Odpowiedzi

2009-12-20T19:46:17+01:00
(x-1)²-(x+4)²=-2x+1
x^2 - 1^2 -x^2 -4^2 = -2x + 1
-1^2 -4^2 = -2x + 1
1- 16 -1= -2x
-16= -2x
2x=16
x=8

............................
(x+1)²+(x-3)(x+3)-2=2(x-1)²
x^2 + 1^2 + x^2 +3x -3x -9 -2 = 2x^2 - 2^2
2x^2 + 1 -9 -2 = 2x^2 -4
2x^2-2x^2 = -4 -1 +9 +2
0 = 6 to jest nierówność
..................................
(x+3)²-(4-x)(4+x)=2(X-1)²+1
x^2 +3^2 -16 -4x +4x -x^2 = 2x^2 - 2^2 +1
x^2 + 9 - 16- x^2 = 2x^2 - 4 +1
x^2 -x^2 +x^2 = -4 + 1 -9 + 16
x^2 = 4
x=√4
x=2
Najlepsza Odpowiedź!
2009-12-20T19:52:00+01:00
(x-1)²-(x+4)²=-2x+1
x²-2x+1-(x²+8x+16)=-2x+1
x²-2x+1-x²-8x-16=-2x+1
-10x-15=-2x+1 /+15
-10x=-2x+16 /+2x
-8x=16 :(-8)
x=-2

(x+1)²+(x-3)(x+3)-2=2(x-1)²
x²+2x+1+x²-9-2=2(x²-2x+1)
2x²+2x-10=2x²-4x+2 /-2x²
2x-10=-4x+2 /+4x
6x-10=2 /+10
6x=12 /:6
x=2

(x+3)²-(4-x)(4+x)=2(X-1)²+1
x²+6x+9-(16-x²)=2(x²-2x+1)+1
x²+6x+9-16+x²=2x²-4x-1+1
2x²+6x-7=2x²-4x /-2x²
6x-7=-4x /+7
6x=-4x+7 /+4x
10x=7 /10
x=10/7=1 3/7(jeden i trzy siódme)